2001
DOI: 10.1002/cne.1350
|View full text |Cite
|
Sign up to set email alerts
|

Branchiogenic motoneurons innervating facial, masticatory, and esophageal muscles show aberrant distribution in the reeler‐phenotype mutant rat, Shaking Rat Kawasaki

Abstract: Shaking Rat Kawasaki (SRK) is an autosomal recessive mutant rat that is characterized by cerebellar ataxia. Although previous studies indicated many points of similarity between this mutant rat and the reeler mouse, nonlaminated structures such as the facial nucleus have not been studied in this mutant rat. Nissl-stained sections through the brainstem showed that the cytoarchitecture of the facial, motor trigeminal, and ambiguus nuclei was abnormal in SRK, especially in the lateral cell group of the facial nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
(93 reference statements)
1
8
0
Order By: Relevance
“…Our previous studies demonstrated that ambiguus motoneurons innervating the subdiaphragmatic esophagus of Reelin -deficient animals, reeler and SRK , are more widely distributed compared with their normal counterparts [11,12]. The present study has confirmed that ambiguus motoneurons innervating laryngeal and esophageal muscles of the SRK rats are not only located in the ambiguus nucleus, but also scattered more widely in an arch running between the floor of the fourth ventricle.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our previous studies demonstrated that ambiguus motoneurons innervating the subdiaphragmatic esophagus of Reelin -deficient animals, reeler and SRK , are more widely distributed compared with their normal counterparts [11,12]. The present study has confirmed that ambiguus motoneurons innervating laryngeal and esophageal muscles of the SRK rats are not only located in the ambiguus nucleus, but also scattered more widely in an arch running between the floor of the fourth ventricle.…”
Section: Discussionsupporting
confidence: 93%
“…Of these four components, only the compact formation is recognized in the adult SRK rat [12], and the boundaries of other subnuclei were blurred in this mutant rat due to the displacement of laryngeal and esophageal motoneurons. Furthermore, these subnuclear structures of young pups could not be clearly demarcated even in the normal P21 rat.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations